Ethno-medico botanical study among the four indigenous communities of Bandarban, Bangladesh - Mohiuddin, Mohammed; Alam, Md. Khairul; Basak, Sukla Rani; Hossain, M. Kamal (Bangladesh Journal of Plant Taxonomy, 2012)
This paper provides ethno-botanical information on 70 plant species under 36 families and these species were in common use among the Bwam, the Marma, the Murang and the Tanchangya communities of Bandarban hill district. Ethno-medicinal uses along with their scientific names, families, local names, voucher numbers and uses are enumerated. Quantitative analysis shows that the Marma tribe uses the higher number of species followed by the Tanchangya, the Murang and the Bwam. Similarity index indicates that the Marma, the Tanchangya and the Murang have higher similarities for ethno-botanical knowledge among four tribes. The most widely used medicinal plants are Cassia obtusifolia L., Centella asiatica (L) Urban., Costus speciosus Smith, Emilia sonchifolia DC., Litsea glutinosa (Lour.) Roxb., Melothria indica Lour. and Premna esculenta Roxb. Fever, cough, menstrual problem, diarrhoea, dysentery, tumor and skin diseases seem to be common problems treated using plants by the tribal communities in Bandarban district. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10941 Bangladesh J. Plant Taxon. 19(1): 45-53, 2012 (June)